2020
DOI: 10.3390/ijms21186592
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol-Mediated Changes to the Phospholipid Profile of UVB-Irradiated Keratinocytes from Psoriatic Patients

Abstract: UVB phototherapy is treatment for psoriasis, which increases phospholipid oxidative modifications in the cell membrane of the skin. Therefore, we carried out lipidomic analysis on the keratinocytes of healthy individuals and patients with psoriasis irradiated with UVB and treated with cannabidiol (CBD), phytocannabinoid with antioxidant and anti-inflammatory properties. Our results showed that, in psoriatic keratinocytes phosphatidylcholine (PC), phosphatidylinositol (PI), phosphatidylserine (PS), and ether-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 70 publications
2
32
1
Order By: Relevance
“…The translocation of phospholipids in cell membranes, especially PS, has been recognized as one of the most important markers of the initial phase of apoptosis and is a key signal that triggers phagocytosis in both apoptotic and necrotic cells [58,59]. In addition, the results of our earlier work have shown that CBD treatment of keratinocytes from psoriasis patients causes an increase in SM levels [33]. This finding indicates a correlation between a decrease in PC levels and an increase in SM levels with a reduction in the negative charge of both the epidermis (keratinocytes) and dermis (fibroblasts), which is suggested by the fact that the association constant of negatively charged groups in SM with H + ions has a greater value than the association constant of these groups in PC [60,61].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The translocation of phospholipids in cell membranes, especially PS, has been recognized as one of the most important markers of the initial phase of apoptosis and is a key signal that triggers phagocytosis in both apoptotic and necrotic cells [58,59]. In addition, the results of our earlier work have shown that CBD treatment of keratinocytes from psoriasis patients causes an increase in SM levels [33]. This finding indicates a correlation between a decrease in PC levels and an increase in SM levels with a reduction in the negative charge of both the epidermis (keratinocytes) and dermis (fibroblasts), which is suggested by the fact that the association constant of negatively charged groups in SM with H + ions has a greater value than the association constant of these groups in PC [60,61].…”
Section: Discussionmentioning
confidence: 89%
“…The results of this study showed that both UVA and UVB radiation increased the levels of different classes of phospholipids (PC, PE, PS, and PI) in keratinocytes and fibroblasts from both psoriasis patients and healthy individuals. Similarly, literature data demonstrate that fibroblasts exposed to UVA and UVB radiation as well as keratinocytes exposed to UVB radiation have increased PC and PE levels and decreased sphingomyelin (SM) levels [25,33,39,40]. The increase in the PC level and the decrease in the SM level may be related to the activation of sphingomyelinase, which hydrolyzes SM to ceramides and phosphocholine, a compound that mediates the synthesis of PC and may lead to its increase [41].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is well-known that UV radiation, particularly by the induction of oxidative stress, leads to the alteration of skin phospholipid and ceramide metabolism, and consequent changes in their levels and composition [ 42 ]. Until now, most research has focused on the effect of UV radiation on the phospholipid metabolism in major epidermal cells—keratinocytes [ 32 , 43 , 44 ]. Unfortunately, these studies do not reflect the metabolic consequences of UV radiation in the dermis, the deeper layer of the skin, the primary cells of which are the fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of the amount of phospholipids in each extract was performed according to the Bartlett and Lewis method [ 31 ]. Experimental procedures of lipid extraction and phospholipid quantification were described in detail in a previously published study based on the same methodology [ 32 ].…”
Section: Methodsmentioning
confidence: 99%